Quantitative Study on Iron Reinforcement Waste Utilization for Material Efficiency in Boarding House Structures in Bantul - Rizal Maulana; Sely Novita Sari (Universitas Islam Raden Rahmat, Malang, 2025)
The construction sector is one of the largest consumers of material resources, with reinforcement bars (rebar) contributing significantly to project costs. However, standard cutting practices often generate leftover steel, typically regarded as waste, despite its potential for reuse. This study aims to evaluate the efficiency of reusing rebar waste in the structural components columns, beams, and slabs of a two-story boarding house project in Bantul, Indonesia. A quantitative case study method was applied, analyzing planned versus actual steel usage, and calculating the waste percentage compared to the 5% standard from Indonesia’s AHSP. Field data, including drawings, BoQ, and technical reports, were used to measure actual rebar waste and its financial impact. Results show actual waste levels of 2.17% for columns, 2.55% for beams, and 1.21% for slabs significantly lower than the 5% benchmark. This translates into a cost saving of Rp11,393,643.78 for a medium-scale project. These findings confirm that precise planning and reuse of steel offcuts can minimize waste and promote sustainable construction practices. It is recommended that future projects adopt material reuse strategies and integrate digital tools such as BIM to enhance real-time material tracking and cutting optimization.